Geoeconomical pre-conditions and factors of marine potential of Ukraine formation before the conflict of 2013–2014 - Kopachinska, G. V.; Копачінська, Г. В. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Geoeconomical pre-conditions and factors of Ukrainian marine potential formation are analyzed. Marine position influence on the naval power of Ukraine is considered. The basic problems of the state marine strategy forming are reflected. The overcoming ways of complicated questions about Ukrainian marine potential formation are investigated.

Проаналізовано геоекономічні передумови та чинники формування морського потенціалу України. Вивчено вплив приморського положення України на формування її морського потенціалу. Визначено основні проблеми реалізації морської стратегії держави. Досліджено шляхи подолання проблемних питань формування морського потенціалу держави.
Геоекономічні передумови та чинники формування морського потенціалу України до конфлікту 2013–2014 рр.
Keywords: geoeconomical pre-conditions; marine potential; marine policy; naval power; Ukraine; Black Sea region; energy safety; геоекономічні передумови; морський потенціал; морська політика; Україна; Чорне море; енергетична безпека